PREGNANCY ANEMIA EDUCATION AND MONITORING PROGRAM IN BANDUNGREJOSARI URBAN VILLAGE - Retnaningsih, Reny; Anik Sri Purwanti; Tut Rayani Aksohini Wijayanti; Zainal Alim (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: Anaemia in pregnancy is a major public health issue linked to adverse maternal and neonatal outcomes, particularly in developing countries. In Bandungrejosari Village, Malang City, anaemia affects about 35% of pregnant women. This program aimed to implement community-based education and monitoring programme in improving knowledge, adherence to iron supplementation, and haemoglobin levels. Methods: Community service was conducted with 20 pregnant women purposively selected from Puskesmas Janti. Eligible participants had a gestational age of ≥12 weeks and no haematological disorders. Data were collected using validated questionnaires on knowledge and adherence, and haemoglobin levels were measured using a portable hemoglobinometer. Statistical analysis employed paired t-tests and chi-square tests with a significance level of p < 0.05. Results: The program significantly improved knowledge levels, with mean increases ranging from 38% to 42% (p < 0.001). Adherence to iron supplementation rose from 57% to 90%, while the prevalence of anaemia decreased from 35% to 18%. The mean haemoglobin concentration increased from 10.5 ± 0.8 g/dL to 12.2 ± 0.7 g/dL (p < 0.001). Conclusion: The findings demonstrate that a community-based anaemia education and monitoring programme can effectively enhance knowledge, adherence to supplementation, and haemoglobin status among pregnant women. The authors declare no potential conflict of interest in conducting this study.